The Maastricht Criteria and its alternatives - Tóthová, Jana (2008)
This work deals not only with the issue of the Maastricht Convergence criteria but also with an alternative way of evaluation of the preparedness to monetary integration – the theory of Optimum currency areas. It contains an enumeration of convergence criteria stated in the Maastricht Treaty, explains its purport and imperfections. Further on a few criteria stemming from the Optimum currency area theory are listed and the relation between them and the Maastricht criteria is examined. In the practical part the preparedness of the Czech Republic to enter the Eurozone is evaluated on the basis of both criteria. Emphasis is put on the relation between the Maastricht criteria and the Optimum currency area criteria on both, theoretical and empirical basis